Why Interest Rates Rise When an Unexpectedly Large Money Stock is Announced - Nichols, Donald A.; Small, David H. (American Economic Review, 2016)
ment of an unexpectedly large growth in the money supply will lead to an immediate increase in interest rates. This is often taken as confirmation of the monetarist view that the way to bring down interest rates, even in the short run, is to reduce the rate of money growth. In this paper we provide an alternative explanation of the announcement effect that is consistent with the Keynesian view that, in the short run, the way to bring down interest rates is to expand the money supply. We do not address the issue of inflationary expectations in a formal way, though, in the long run, we would expect the well-known Fisher effect to hold. Looking closely at the announcement effect, it is clear that whatever may be the true short-run relationship between money growth and interest rates, it cannot be inferred from a simple correlation of announcements of changes in the money stock with the resulting changes in interest rates. This is because of several properties of the announcement phenomenon that we capture in the model